2022
DOI: 10.1590/fst.55721
|View full text |Cite
|
Sign up to set email alerts
|

The addition of crude gambir extract in the production of functional robusta coffee powder

Abstract: This study aims to improve the functional properties of robusta coffee by adding crude gambir extract. A completely randomized non-factorial design with 5 treatments is used and each treatment was repeated three times. The treatments consist of: robusta coffee powder (%): crude gambir extract (%) F1 = 100:0, F2 = 95:5, F3 = 90:10, F4 = 85:15, and F5 = 80:20. The results showed that the addition of crude gambir extract has a significant effect on increasing the total phenol value from 10.65 to 101.20 mg/mL GAE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…As shown in Table 1, with the introduction of coffee or cocoa, the mellowness and matureness of aroma, as well as the fluentness and sweetness of smoke in cigar were improved obviously. It indicated that fermented additives contributed significantly to the perceived sensory characteristics of cigar, which was owing to the chemical profile of additives (Santoso et al, 2022;Seçuk & Seçim, 2022). Therefore, in addition to sensory quality, it is also significant to analyze the effects of coffee and cocoa on the chemical profile of tobacco leaves.…”
Section: Sensory Quality Evaluationmentioning
confidence: 99%
“…As shown in Table 1, with the introduction of coffee or cocoa, the mellowness and matureness of aroma, as well as the fluentness and sweetness of smoke in cigar were improved obviously. It indicated that fermented additives contributed significantly to the perceived sensory characteristics of cigar, which was owing to the chemical profile of additives (Santoso et al, 2022;Seçuk & Seçim, 2022). Therefore, in addition to sensory quality, it is also significant to analyze the effects of coffee and cocoa on the chemical profile of tobacco leaves.…”
Section: Sensory Quality Evaluationmentioning
confidence: 99%
“…To solve these problems, several studies have been carried out on the organic chemistry of natural products, developing solvent formulations that are less harmful to the environment, and replacing conventional organic solvents in the extraction of bioactive substances from plant species (Belwal et al, 2018;Chanioti & Tzia, 2018;Choi & Verpoorte, 2019;Santoso et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In the course of this relatively simple process, a series of events occur in line with the roasting process, causing the green bean to completely change its structure to release the coffee-forming compounds in the cup (Pereira et al, 2021b). It creates the organoleptic characteristics of coffee, which is the most important factor influencing the consumer appeal of a coffee drink (Santoso et al, 2022).…”
Section: Introductionmentioning
confidence: 99%